Tinjauan Yuridis Terhadap Gesek Tunai Pada Kartu Kredit Sebagai Alat Pembayaran (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Cash swipe is a practical way to deal with the high cost of withdrawals at ATMs. Becausewithdrawing credit card cash from an ATM machine will be exposed to a very high interest expense,whereas if the credit card holder does cash swipe at the merchant the fee that will be charged to the cardholder is only 3% for each transaction. In the city area of Pekanbaru itself there are many shops thatprovide cash swipe services. Since the issuance of the latest PBI regulation governing credit cards, namelyPBI Number 14/2 / PBI / 2012 concerning the Implementation of Card-Based Payment Instruments, the useof credit cards other than as a means of payment is expressly prohibited by Bank Indonesia. The purpose ofwriting this thesis, namely; First, to find out the causes of the practice of cash friction is still mostly done inthe community, Secondly, to find out the legal consequences of the practice of cash friction using creditcards.This type of research can be classified in the type of sociological juridical research, because in thisstudy the author immediately conducted research at the location or place under study in order to provide acomplete and clear picture of the problem under study. This research was conducted in the area ofPekanbaru City, while the population and samples were all parties related to the problems examined in thisstudy, data sources used, primary data, secondary data, and tertiary data, data collection techniques in thisstudy with interviews, questionnaire, and literature review.Based on the results of the research problem, there are two main things that can be concluded.First, many of the causes of cash swift practice are still carried out by the community, such as; fees chargedto cardholders are cheaper; no withdrawal limit; places that receive cash swipe services can be easilyfound. Second, the regulations issued regarding the prohibition to conduct cash swipe transactions arecontained in PBI No. 11/11 / PBI / 2009 as amended by PBI No. 14/2 / PBI / 2012. If violating will besubject to administrative sanctions. The author's advice, First, should the card holder avoid withdrawal offunds through cash swipes. Second, the merchant is expected to be honest in doing business. Thirdly, thebank that issues katu is expected to comply with the rules and educate merchants about the ban on providingcash friction services, fourth , BI is expected to increase the supervision and control of credit card issuingbanks so there will be no more abuse in using credit cards.Keywords: Swipe Cash - Credit Card - Payment Tool